Microprocesses of Institutional Change in the Context of Privatization - Johnson, Gerry; Smith, Stuart F.; Codling, Brian S. (Academy of Management Review, 2000)
Conceptualizing privatization as the shift from one institutional template to another, we draw on the related literature of institutional theory and script development to explore the interactive effects of actors' behavioral scripts and institutional templates. In so doing, we address microlevel aspects of the macroinstitutional change of privatization and advance our understanding of the role of public sector managers in the privatization process.